2023
DOI: 10.1002/advs.202300588
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein and Glycan Packaging into Extracellular Vesicles in Response to 3D Gastric Cancer Cellular Organization

Abstract: Alterations of the glycosylation machinery are common events in cancer, leading to the synthesis of aberrant glycan structures by tumor cells. Extracellular vesicles (EVs) play a modulatory role in cancer communication and progression, and interestingly, several tumor‐associated glycans have already been identified in cancer EVs. Nevertheless, the impact of 3D tumor architecture in the selective packaging of cellular glycans into EVs has never been addressed. In this work, the capacity of gastric cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Similar patterns were found for gastric cancer. Here, RNA signatures identified in EVs that were isolated from 3D cultures correlated with CIN and poor patient survival, further underscoring the potential of EVs in detecting CIN + cancers [112]. While many other factors in EVs will play a role in shaping the TME, collectively, these findings highlight the potential role of EVs as messengers and as promising biomarkers to detect CIN + cancers.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 66%
See 1 more Smart Citation
“…Similar patterns were found for gastric cancer. Here, RNA signatures identified in EVs that were isolated from 3D cultures correlated with CIN and poor patient survival, further underscoring the potential of EVs in detecting CIN + cancers [112]. While many other factors in EVs will play a role in shaping the TME, collectively, these findings highlight the potential role of EVs as messengers and as promising biomarkers to detect CIN + cancers.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 66%
“…Prior work has revealed many important interactions between CIN and EVs [83,[111][112][113]. As an example, amplification of centrosomes, another driver of CIN, triggers increased secretion of small extracellular vesicles (SEVs) as a result of lysosomal dysfunction and increased levels of ROS [88].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…To test our hypothesis that cancer cells release distinct types of EVs over the course of invasive transition, we utilized an ECM‐based 3D culture method for studying secretion of EVs from PC3 prostate cancer tumoroids undergoing invasion. Previously used 3D culture models for EV studies have utilized synthetic hydrogels (Kyykallio et al., 2022 ; Millan et al., 2022 ; Thippabhotla et al., 2019 ), polymeric hard scaffolds (Eguchi et al., 2018 ; Martins et al., 2023 ), and scaffold‐free approaches (Giusti et al., 2022 ; Rocha et al., 2019 ), which allow the cells to form solid tumours, but impede invasion. In the ECM‐based hydrogel Matrigel, PC3 prostate cancer cells form tumoroids that over the course of the culture period invade the surrounding hydrogel, as shown in our previous study (Björk et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, three‐dimensional (3D) cell culture models provide a more accurate representation of tumour characteristics, allowing cancer cells to acquire similar morphology, growth and differentiation patterns as those detected in tumours (Duval et al., 2019 ). It is therefore no surprise that multiple studies have shown substantial differences in the secretion and cargo components of EVs between 2D and 3D cancer cell cultures (Al Hrout et al., 2023 ; Eguchi et al., 2018 ; Giusti et al., 2022 ; Kyykallio et al., 2022 ; Martins et al., 2023 ; Millan et al., 2022 ; Rocha et al., 2019 ; Szvicsek et al., 2019 ; Thippabhotla et al., 2019 ; Yang et al., 2020 ). These studies employed synthetic hydrogels and scaffolds, as well as extracellular matrix (ECM)‐based 3D cultures, but it remains to be shown whether EV secretion and characteristics change during tumour development and invasive transition.…”
Section: Introductionmentioning
confidence: 99%